Nucleosomes Are Translationally Positioned on the Active Allele and Rotationally Positioned on the Inactive Allele of the HPRT Promoter - Chen, Chien (American Society for Microbiology, 2001)
Differential chromatin structure is one of the hallmarks distinguishing active and inactive genes. For the X-linked human hypoxanthine phosphoribosyltransferase gene (HPRT), this difference in chromatin structure is evident in the differential general DNase I sensitivity and hypersensitivity of the promoter regions on active versus inactive X chromosomes. Here we characterize the nucleosomal organization responsible for the differential chromatin structure of the active and inactive HPRT promoters. The micrococcal nuclease digestion pattern of chromatin from the active allele in permeabilized cells reveals an ordered array of translationally positioned nucleosomes in the promoter region except over a 350-bp region that is either nucleosome free or contains structurally altered nucleosomes. This 350-bp region includes the entire minimal promoter and all of the multiple transcription initiation sites of the HPRT gene. It also encompasses all of the transcription factor binding sites identified by either dimethyl sulfate or DNase I in vivo footprinting of the active allele. In contrast, analysis of the inactive HPRT promoter reveals no hypersensitivity to either DNase I or a micrococcal nuclease and no translational positioning of nucleosomes. Although nucleosomes on the inactive promoter are not translationally positioned, high-resolution DNase I cleavage analysis of permeabilized cells indicates that nucleosomes are rotationally positioned over a region of at least 210 bp on the inactive promoter, which coincides with the 350-bp nuclease-hypersensitive region on the active allele, including the entire minimal promoter. This rotational positioning of nucleosomes is not observed on the active promoter. These results suggest a model in which the silencing of the HPRT promoter during X chromosome inactivation involves remodeling a transcriptionally competent, translationally positioned nucleosomal array into a transcriptionally repressed architecture consisting of rotationally but not translationally positioned nucleosomal arrays.